Towards Student-Centred Learning: Factors Contributing to the Adoption of E-Learn@USM - Ng, See Kee; Omar, Bahiyah; Mohamed, Ramli (Penerbit Universiti Sains Malaysia, 2012)
In 2009, Universiti Sains Malaysia (USM) launched E-Learn@USM, an electronic system for delivering and sharing learning materials as well as engaging lecturers and students in online discussions. Rather than replacing the traditional face-to-face classroom method, the role of E-Learn@USM is to foster student-centred learning, which is lauded for its effectiveness in the educational setting. The current study aims to examine factors contributing to the adoption of E-Learn@USM among USM students. The factors are categorised into individual factors (personal innovativeness, self-efficacy and attitude), organisational factors (university, administrator and instructor supports), and technological factors (relative advantage, compatibility, complexity, trialability and observability). These factors were selected based on the Diffusion of Innovations Theory and on previous studies on adoption within the innovation-diffusion framework. Using multistage cluster sampling, a survey was conducted on a total of 495 students sampled from a large population of undergraduate students at USM. The results of the hypothesis testing revealed significant relationships between all factors (except for complexity) and the adoption of E-Learn@USM. Five significant predictors – attitude, university support, trialability, relative advantage and self-efficacy – were identified.